Ana Vicente Sánchez, Las Cartas de Temístocles. Lengua y Técnica compositiva (Monografías de Filología Griega-17), Zaragoza 2006, 484 págs. ISBN 84-96214-74-5 (Minerva, 2019)
Review: Ana Vicente Sánchez, Las Cartas de Temístocles. Lengua y Técnica compositiva (Monografías de Filología Griega-17), Zaragoza 2006, 484 págs. ISBN 84-96214-74-5